Analisa Pengaruh Virtual Reality Terhadap Perkembangan Pendidikan Indonesia - Charles Charles; Delvian Yosuky; Tio Sania Rachmi; Eryc Eryc (Journal Innovation In Education, 2023)
The rapid advancement of technology has brought the integration of Virtual Reality (VR) into various educational sectors worldwide, including Indonesia. The focus of this research is to evaluate the impact of using Virtual Reality on the educational development in Indonesia. Through a comprehensive literature review and empirical analysis, this study discusses the potential benefits and challenges that may arise from the implementation of VR technology in the educational context. Furthermore, this research also investigates how VR can enrich traditional teaching methods, engage students in a profound learning process, and enhance their understanding of complex concepts.This research contains an analysis of the influence of virtual reality on the development of education in Indonesia, where the researchers will distribute online questionnaires and gather samples of respondents to conclude questions related to virtual reality. This study will contribute to the existingliterature, especially on the factors that influence the adoptionof Virtual Reality for Media Learning model.